2012
DOI: 10.1590/s0102-37722012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Análise de erros e compreensão de textos: comparações entre diferentes situações de leitura

Abstract: RESUMO -O presente estudo analisou os erros apresentados por crianças com dificuldades de compreensão de textos em duas situações de leitura. As crianças do Grupo 1 realizaram a leitura interrompida de uma história e as do Grupo 2 realizaram a leitura sem interrupção. Após a leitura, as crianças responderam perguntas sobre informações inferenciais. A análise das respostas permitiu identificar quatro tipos de erros referentes à maneira de integrar informações intra e extratextuais. Apesar dos erros serem estáve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
2
6
0
4
Order By: Relevance
“…It was observed, when comparing the total means of the groups, that there was more difficulty for inferential questions, as it was suggested in the hypothesis of this study. This corroborates the literature which reports that comprehension is a constructive and integrative process, and skilled readers do it spontaneously, inferences to link ideas and information which are implied, and this is a necessary process to form the integrated representation of a text 2,[9][10][11][12] . When the performances of the students from all groups were compared, according to text genre, it was found that the average sum of the inferential questions from two narrative texts was higher than the sum average of the expository texts inferences.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It was observed, when comparing the total means of the groups, that there was more difficulty for inferential questions, as it was suggested in the hypothesis of this study. This corroborates the literature which reports that comprehension is a constructive and integrative process, and skilled readers do it spontaneously, inferences to link ideas and information which are implied, and this is a necessary process to form the integrated representation of a text 2,[9][10][11][12] . When the performances of the students from all groups were compared, according to text genre, it was found that the average sum of the inferential questions from two narrative texts was higher than the sum average of the expository texts inferences.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, data suggested that these students had difficulty for selecting the correct alternative, when answering the questions of the text, even though, failing to notice the macro-structure necessary for inferences formation, the answer did not seem clear to the students, also corroborating previous studies which showed the same difficulties 9,10,12 .…”
Section: Discussionsupporting
confidence: 72%
“…Dialogic reading is an intervention package, and one limitation of this study is that it did not attempt to separate the effects of different components of dialogic reading. There is evidence, for example, that pauses during shared reading, of and by themselves, may be beneficial for text comprehension (Spinillo & Hodges, 2012). As Gast (2010) recommends, if we wish to describe the independent variable and its effects with replicable precision, it is necessary to investigate which characteristics of an intervention package are crucial for specific results.…”
mentioning
confidence: 99%
“…The importance attributed to these aspects stems from the fact that it is necessary to master writing encoding and decoding processes in order for the learner to advance in a process of understanding 13 and text production. Such processes certainly refer to major skills involved in the necessary linguistic analysis in order to master reading and writing, which is made possible by an array of complex factors involved in the acquisition of the written language 14 .…”
Section: Discussionmentioning
confidence: 99%